Nowoczesne przedsiębiorstwo : wyzwania organizacyjne i technologiczne w warunkach globalnej konkurencji - Niesler, Andrzej (Modern Enterprise : Organizational and Technological Challenges of Global Competition, 2007)
This paper considers global trends in economic and information environment of modem enterprises. The main goal is to identify and analyze the impact of organizational and technological changes and enumerate activities that have to be undertaken in order to face the present and upcoming challenges of global market competition.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (11); 2007; nr 1156, s. 40-47